Improving Students’ Oral Communication Abilities Through the implementation of Debate Strategies - Muxammadiyeva Halima Saidaxmadovna (Scientific Trends, 2024)
Language Proficiency and communicative skills have always been a benchmark of ELT all over the world. Enhancing learners' communicative skills through stimulating and encouraging students to interact in the target language is both possible and effective and cooperative learning principles can be adopted in EFL classrooms. As David Nunan stated that language is acquired as learners actively interact with each other to communicate in target language. This article is aimed to find out how much debate can contribute significantly to improve the students’ speaking skill achievements.
Keywords: Debate, speaking, speaking skill, critical thinking, EFL classroom.